The Effect of Complete Feed on Dry Matter Intake (DMI), Crude Protein Intake (CPI) and Metabolite Status in Female Fat-Tail Sheep - Poespitasari Hazanah Ndaru; Veronica Margareta Ani Nurgiartiningsih; M. Halim Natsir; Mashudi Mashudi; Irida Novianti; John Miftah Ahmad (Postgraduate, University of Mataram, 2026)
This study aimed to evaluate dry matter intake (DMI), crude protein intake (CPI), and metabolite status, including blood urea nitrogen (BUN), glucose, and total protein, in female fat-tail sheep fed a complete feed. The study was conducted from July to September 2022 at a farmer group managed by PT Juara Agroniaga in Kanor Village, Bojonegoro Regency, East Java, Indonesia. A total of 200 female fat-tail sheep aged 1–2.5 years with an average body weight of 27 ± 4.65 kg were reared in 10 group pens (20 animals per pen). Feed intake was recorded daily for six weeks, and blood samples were collected to determine BUN, glucose, and total protein. Data were analyzed descriptively. The results showed that DMI and CPI were 71.00 ± 5.88 and 6.83 ± 0.57 g/kg BW0.75, respectively. Metabolite status showed BUN of 25.15 ± 6.94 mg/dL, glucose of 83.83 ± 14.43 mg/dL, and total protein of 4.54 ± 2.58 g/dL. The complete feed was consumed at an acceptable level under farmer conditions, as reflected by the observed DMI. however, the high fiber content and relatively low crude protein level may have contributed to suboptimal metabolite profiles. In conclusion, the nutritional quality of the complete feed influenced nutrient intake and was reflected in the metabolite status of female fat-tail sheep